Standards and Procedures surrounding the Disqualification of Arbitrators under ICSID Rules - Jiménez F., Dyalá (2025)
The independence and impartiality of arbitrators are essential pillars for the legitimacy of international arbitration. Within the ICSID framework, challenges to the lack of independence and impartiality of arbitrators are examined through disqualification proposals and annulment proceedings. This article examines the rules and practice of disqualification under the ICSID Convention, both pursuant to the 2006 Arbitration Rules and the version that entered into force in 2022, to illustrate how the mechanism operates under the ICSID Convention and what changes have brought greater clarity and speed to the conduct of the proceedings.